Workplace spirituality among Malaysian employees in hospitality and educational organisations - Ahmad, Aminah; Omar, Zoharah; Jamal, Nur Aien (Universiti Putra Malaysia Press, 2018)
There is an increasing interest in spirituality at work for the past decade as individuals seek to live out their spiritual values in the workplace. Despite its importance as an individual experience that may be unique in different work settings for different individuals, it has not received adequate attention in organisational studies. This study examines the experience of spirituality (meaningful work, sense of community and alignment of values) among employees in two selected service industries, specifically the hospitality and education industries in Malaysia. Data were collected from 198 employees using a self-administered questionnaire and analysed using descriptive statistics and an independent sample t-test. The overall level of workplace spirituality among employees in the educational organisations was higher than that in the hospitality organisations. We found that there were differences in the experience of work as meaningful, sense of connectedness with others at work and alignment of personal and organisation's values between employees in the educational and hospitality organisations. The results have implications for organisations in developing and planning practices aimed at nurturing spirituality at work.